Predictive factors of nonfatal self-harm among community-dwelling older adults assessed for support services. (18th September 2022) - Cheung, Gary; Chai, Yi; Troya, M. Isabela; Luo, Hao
ABSTRACT: Background: Older adults receiving support services are a population at risk for self-harm due to physical illness and functional impairment, which are known risk factors. This study aims to investigate the relative importance of predictive factors of nonfatal self-harm among older adults assessed for support services in New Zealand. Methods: interRAI-Home Care (HC) national data of older adults (aged ≥ 60) were linked to mortality and hospital discharge data between January 1, 2012 and December 31, 2016. We calculated the crude incidence of self-harm per 100, 000 person-years, and gender and age-adjusted standardized incidence ratios (SIRs). The Fine and Gray competing risk regression model was fitted to estimate the hazard ratio (HR; 95% CIs) of self-harm associated with various demographic, psychosocial, clinical factors, and summary scales. Results: A total of 93, 501 older adults were included. At the end of the follow-up period, 251 (0.27%) people had at least one episode of nonfatal self-harm and 36, 333 (38.86%) people died. The overall incidence of nonfatal self-harm was 160.39 (95% CI, 141.36–181.06) per 100, 000 person-years and SIR was 5.12 (95% CI, 4.51–5.78), with the highest incidence in the first year of follow-up. Depression diagnosis (HR, 3.02, 2.26–4.03), at-risk alcohol use (2.38, 1.30–4.35), and bipolar disorder (2.18, 1.25–3.80) were the most significant risk factors. Protective effects were found with cancer (0.57, 0.36–0.89) and severe level of functional impairment measured by Activities of Daily Living (ADL) Hierarchy Scale (0.56, 0.35–0.89). Conclusion: Psychiatric factors are the most significant predictors for nonfatal self-harm among older adults receiving support services. Our results can be used to inform healthcare professionals for timely identification of people at high risk of self-harm and the development of more efficient and targeted prevention strategies, with specific attention to individuals with depression or depressive symptoms, particularly in the first year of follow-up.